Small-Scale Surface (Tank) Irrigation in Asia - Palanisami, K.; Easter, K. William (American Geophysical Union, 1987)
Tank irrigation is an ancient tradition in Asia which is now being reviewed as a potential model for future irrigation expansion. South India has thousands of tanks which are in need of rehabilitation after being in operation for over a century. This study evaluates tank irrigation in an area of south India which has the greatest concentration of tanks. Constraints and unique characteristics of tank irrigation are analyzed to provide a basis for devising strategies for improving tank irrigation. A combination of public and private investments along with institutional changes are recommended to help farmers organize to improve irrigation. Yet, only if public investment is carefully integrated with existing private efforts will farmers have incentives to maintain the irrigation systems.